2012
DOI: 10.1590/s1984-46702012000200004
|View full text |Cite
|
Sign up to set email alerts
|

Replacement and growth of primary feathers in captive rock pigeons, Columba livia (Aves: Columbidae)

Abstract: ABSTRACT. The replacement and growth of 311 primary feathers of eight captive male rock pigeons, Columba livia Gmelin, 1789 were monitored daily. Feather replacement was recorded in all months, but the primaries 1 to 5 (innermost primaries) were replaced mostly from September to December, whereas the primaries 6 to 10 (outermost primaries) were more frequently replaced from January to August. Each primary was held in plumage from six to fifteen months, but the lifetime of the outer feathers was longer than tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Males added 19.5 mm/d and females added 15.7 mm/d to the total length of all primaries during this linear growth phase. This equates to an average per-primary growth rate of 4.4 mm per day for females and 5.5 mm per day for males, which is similar to the 4-5 mm per primary remex per day reported for molt in other species (Dawson 2003, Mallet-Rodrigues 2012.…”
Section: Figsupporting
confidence: 72%
“…Males added 19.5 mm/d and females added 15.7 mm/d to the total length of all primaries during this linear growth phase. This equates to an average per-primary growth rate of 4.4 mm per day for females and 5.5 mm per day for males, which is similar to the 4-5 mm per primary remex per day reported for molt in other species (Dawson 2003, Mallet-Rodrigues 2012.…”
Section: Figsupporting
confidence: 72%
“…In one of the authors’ experience, and likewise noted by colleagues, manually pulling damaged feathers can induce feather regrowth, even outside of the natural moulting period 42 43. A study in rock pigeons reported that primary flight feathers accidentally pulled during handling typically began to regrow within 8 days 44…”
Section: Discussionmentioning
confidence: 89%
“…42 43 A study in rock pigeons reported that primary flight feathers accidentally pulled during handling typically began to regrow within 8 days. 44 In an attempt to accelerate the rehabilitation process, the feather-pull method of moult induction was utilised for several secondary covert feathers in the GHOW in our study but failed to stimulate regrowth. Although feather pulling often induces regeneration, it may also produce the opposite effect.…”
Section: Outcome and Follow-upmentioning
confidence: 90%
“…In general terms, turtle doves nest in trees or bushes in a landscape characterized by a patchy habitat mosaic of open land, nearby to wooded areas and an adjacent water source (Lutz 2007;Fisher et al 2018). Habitat selection patterns and habitat requirements were investigated by numerous studies mainly based on observational absence and presence data (Supplementary Table 4).…”
Section: Breeding and Wintering Areasmentioning
confidence: 99%